Enabling Multiple Outcomes: Strategic Spatial Planning in a Shrinking City-Region - Oittinen, Janne (2024)
The population of Finland will start to decline in the near future, and most Finnish municipalities are already losing population. Can the tools used for land-use planning, which are historically designed to guide and control growth, be used to guide shrinking? The shrinking city-region of Kotka-Hamina has drafted a city-regional strategic master plan to manage the shrinking. The master plan and its documents are analyzed, and interviews are used to better understand how the plan is trying to achieve its objectives. The master plan is currently growth-oriented and used as a tool for place marketing. According to the interviews, growth is not essential to implement the plan. As a tool, it strives to show the potential of the city-region. The master plan guides future land use to denser areas and enables industry. Learning from this case study, strategic land-use planning can be seen as a feasible tool to manage shrinking, and the master plan hints at how that might be done, although it does need improvement. Since land-use planning has country-specific characteristics, the research findings may not be directly transferable to other planning systems. However, the findings may offer ideas on how planning tools can be adapted to similarly challenging conditions. The possibility of what strategic spatial planning has to offer in a shrinking context should be researched more to enable the development of planning tools that would be more usable in shrinking conditions.